A influência das lógicas institucionais nos resultados do Programa Minha Casa Minha Vida (PMCMV) enquanto ambiente complexo - Toresani, Rogério (2017)
Public policies occur in pluralistic environments because the implementation of initiatives depends on different actors with interests and objectives, sometimes conflicting. Such differences are motivated by the fact that the parties act according to their own or shared institutional logic. In this sense, the conflict between institutional logics enhances an institutional complexity, which can be divided into organizational complexity and environmental complexity. The implications of institutional complexity, among them, the sharing of power by stakeholders in public policy make its effective implementation a challenge to government managers. Based on this context, it is examined how the institutional complexity, based on the institutional logics of each actor involved, influences the effectiveness of a brazilian public housing policy. The focus is on public housing policy named Programa Minha Casa Minha Vida (PMCMV). It is a qualitative and descriptive research characterized by a multiple case study. Data were collected from interviews, participant observation and documents. The findings highlight the preponderance of seven institutional logics: 1) state as provider of housing, 2) political-governmental, 3) quality of the ventures, 4) banking-commercial, 5) best financial return, 6) social right, e 7) greatest efficiency between expenditure and political image. Conclusions have demonstrated the need for additional mechanisms to keep actors tied to the common objectives of the public policy in question. On the other hand, it was verified that the performance of these actors is directly related to their private interests, which translates into worse housing and living conditions for the beneficiary families, with negative impacts on PMCMV results. Finally, improvement actions are suggested, based on the results identified.